Cálculo diferencial e integral no movimento dos planetas - Ravagnani, Fábio Araújo [UNESP] (2014)
This work is related to the planets movements, using Kepler's laws through Differential and Integral Calculus. Starting with a historical approach of leading researchers on this field. Afterwards key concepts taken from Calculus and Kepler's law are introduced. In addition to that, activities related to the planets movements were performed with high school students as well as a computer software on this area was used to instigate such students to think about this subject